The Motives of Violence in the Novel Perempuan Kamar By Agus Subakir - Risa Anjelitha Ashar; Inriati Lewa; Syafri Badaruddin (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aims to reveal the motive for the occurrence of violence in the novel Perempuan Kamar by Agus Subakir. This novel is written in Indonesian and includes works of interest. It was firstly published in 2020. The data collection method used in this study is the literature study method. The data of this research are in the form of pieces of texts from works that show violence. The data analysis method used in this research is the descriptive qualitative method. The type of data that will be used in this research is in the form of words, phrases, sentences, and paragraphs that have a direct relationship with the motive for the occurrence of violence in the novel. The results showed that there were two or three motives for the occurrence of violence, namely (1) a sense of hatred towards the victim, (2) an unfulfilled excessive obsession, and (3) a lack of resistance from the victim.